Total Synthesis of PF1163B - Sengupta, Aakash; Hosokawa, Seijiro (Synlett, 2019)
A total synthesis of PF1163B has been achieved. The vinylogous Mukaiyama aldol reaction of ketene silyl N,O-acetal 6 (ent-6) mediated by excess TiCl4 proceeded with saturated aldehydes to give adduct 10 in moderate yield with moderate stereoselectivity. The major isomer is the diastereomer that was provided by using one equivalent of TiCl4. The Birch reduction of α,β-unsaturated imide 4, possessing a less hindered side chain, gave 12 in good stereoselectivity by employing 2-isopropylbenzimidazole as a bulky proton source. After elongation of the carbon chain and connection with the amino acid part, we accomplished a total synthesis of PF1163B. These methods constitute a concise synthetic route to obtain polyketides as well as depsipeptides.
Keywords: PF1163B; total synthesis; vinylogous Mukaiyama aldol reaction; bulky proton source; depsipeptide; stereoswitching